Binding of anions in triply interlocked coordination catenanes and dynamic allostery for dehalogenation reactions. Issue 4 (12th December 2017) - Yang, Linlin; Jing, Xu; An, Bowen; He, Cheng; Yang, Yang; Duan, Chunying
Abstract : Triply interlocked metal organic catenanes with several kinds of individual pockets enabled the possibility of encapsulating different anions, allowing the dynamic allostery between the unlocked/locked conformers to efficiently promote the dehalogenation reaction. Abstract : By synergistic combination of multicomponent self-assembly and template-directed approaches, triply interlocked metal organic catenanes that consist of two isolated chirally identical tetrahedrons were constructed and stabilized as thermodynamic minima. In the presence of suitable template anions, the structural conversion from the isolated tetrahedral conformers into locked catenanes occurred via the cleavage of an intrinsically reversible coordination bond in each of the tetrahedrons, followed by the reengineering and interlocking of two fragments with the regeneration of the broken coordination bonds. The presence of several kinds of individual pocket that were attributed to the triply interlocked patterns enabled the possibility of encapsulating different anions, allowing the dynamic allostery between the unlocked/locked conformers to promote the dehalogenation reaction of 3-bromo-cyclohexene efficiently, as with the use of dehalogenase enzymes. The interlocked structures could be unlocked into two individual tetrahedrons through removal of the well-matched anion templates. The stability and reversibility of the locked/unlocked structures were further confirmed by the catching/releasing process that accompanied emission switching, providing opportunities for the system to be a dynamic molecular logic system.